Murtagh : world of Eragon - Paolini, Christopher (Paolini, Christopher. Inheritance, 2023)
Join Dragon Rider--and fan favorite--Murtagh and his dragon as they confront a perilous new enemy! The world is no longer safe for the Dragon Rider Murtagh and his dragon, Thorn. An evil king has been toppled, and they are left to face the consequences of the reluctant role they played in his reign of terror. Now they are hated and alone, exiled to the outskirts of society.